Tool path cutting strategy for milling aircraft components using aluminium 7050 - Alsultaney, Hazem K. (2010)
Aerospace industry is a value-added and technology integrated industry. In addition, it is a technique-intensive, capital-intensive, and labor-intensive industry. It also integrates the mechanical, electronic, material, chemical and information technology. The old aircraft consist of a lot of components from the sheet metal components which nowadays is being replacing with a thin walled monolithic structure. The thin walled parts normally come from the single billet material and are machined to it intended shape using the high speed milling machine. Improper parameter setting and the way of the part machined will determined the quality of the finished product. The tool path i.e. machining sequence plays a key role in avoiding these problems as it help to minimize the workpiece vibration during machining. This work aims to verify the simulation of finite element analysis (FEA) with an experimental works in order to determine the best machining sequence for the cutting process. It is proven that by using FEA software the optimized tool path can be obtained as it is agreed with the experimental work. The simulated FEA not only can be used for the Macro milling but also suitable for the Micro milling. Tests such as tensile, harness and surface roughness test are carried out to confirm the finding.